Determining Purchase Decisions: Brand Image and Trust (Marketing Management Literature Review) - M. Ridho Mahaputra; Hapzi Ali; Ridho Rafqi Ilhamalimy (Siber Nusantara Research, 2024)
The purpose of writing this Literature Review Paper is to determine the influence of Electronic Word Of Mouth and digital marketing variables on purchasing decisions. Using qualitative methods and Library Research. The research results show that green marketing influences purchasing decisions, digital marketing influences purchasing decisions, Electronic Word Of Mouth and digital marketing together influence purchasing decisions.